Evaluation and comparison of postmortem hydrocodone concentrations in peripheral blood, central blood and liver specimens: A minimal potential for redistribution. (February 2015) - Saitman, Alec; Fitzgerald, Robert L.; McIntyre, Iain M.
Highlights: Hydrocodone distribution in peripheral blood, central blood and liver was studied. When detected, dihydrocodeine was 29% of the hydrocodone concentration. Central to peripheral blood ratios were well correlated with a median value of 1.2. Liver to peripheral blood ratios were well correlated with a median of 3.0 L/kg. This low L/P ratio suggests that hydrocodone is unlikely to undergo substantial PMR. Abstract: Postmortem changes can alter the concentration of drugs in the vascular compartment as compared with concentrations originally present at the time of death. Numerous drugs have been reported to increase due to postmortem redistribution (PMR). The potential for PMR of hydrocodone, a therapeutic opioid analgesic used to manage pain, is of particular interest due to its wide use. Hydrocodone concentrations in 39 peripheral blood, central blood, and liver specimens were compared. Dihydrocodeine (DHC), a commonly encountered hydrocodone metabolite, was present in 61% of the cases with an average concentration that was 29% of the hydrocodone value. Central blood to peripheral blood hydrocodone ratios were well correlated ( R 2  = 0.965) with an average (±S.D.) of 1.3 (±0.35) and a median of 1.2. The liver to peripheral blood (L/P) hydrocodone ratio was also well correlated ( R 2  = 0.915) with an average (±S.D.) of 3.4 (±1.7) L/kg and a median of 3.0 L/kg. This low L/P ratio suggests that hydrocodone is unlikely to undergo substantial PMR changes.